If it's not what You are looking for type in the equation solver your own equation and let us solve it.
z in (-oo:+oo)
(-3/7)*z = -2/9 // + -2/9
(-3/7)*z-(-2/9) = 0
(-3/7)*z+2/9 = 0
2/9-3/7*z = 0 // - 2/9
-3/7*z = -2/9 // : -3/7
z = -2/9/(-3/7)
z = 14/27
z = 14/27
| 7/p=0 | | 7/p-0 | | 11-2=75 | | -6y+5(-2y+3)=8-7(-7-y) | | -15=5q(3q-10)-5q | | 7x-3(5x-(5+x))=1-4x | | 3(w+15)= | | 9z+14z+-17=6 | | x-4=10/3 | | -4n=25 | | (r+3)-5=-4 | | 3x-5+9x=9x+15+36 | | 6+(6-2)+6= | | (r+3)-5=4 | | (5x-7)/3=6 | | -10=5w(2w-4) | | -w^2+7w-12=0 | | -2.1v-2.3=1.2+4.3 | | 2.4=0.8x+3.2 | | 1/3x-2/3=0 | | 5+3x-9=6x-4 | | x=75p+3550 | | 3n+7n=0 | | (K-1)(k-6)= | | S-8/2=3 | | 3(x)-7=83 | | 0=-w^2+4w-3 | | 10t-22=-5(-2t+3) | | -2w=-3w-7 | | 2/3x+3/4=3/5(x-5/8) | | 5(2x+3)-6+6-3(3x-1)-8=x+10 | | 4n-2.8=6.8 |